International Relation and Theory - Lata, Dr Kusum (Innovative Research Thoughts, 2018)
In International Relations (IR) theory, norms are widely held to be the opposite to ‘interest defined as power’ (Morgenthau). Norms are often held to be scripts of emancipation, and power to be a practice of domination. The paper argues that IR norms research all too often buys into a problematic dichotomy by adopting a binary perspective from which power is either held to be superior to norms or erased from the notion of the norm. The problem with this dichotomy is that norms are misconceived when limited to the two options of either being emancipatory values against the dictates of power politics or utopist scripts never standing these dictates in the long run. The paper aims to explore a deeper understanding of how norms are political and how elements like power, coercion, and violence circulate within norms and norms-related practice. To this end, it offers IR to draw on certain strands of work in legal theory, namely the legacies of American legal realism and critical legal studies, to elaborate on how norms and norms-related practice are political.